Strategies and Consequences of Non-Marriage among Men: A Grounded Theory Study - Mansourzadeh, Sayedeh Zahra; Nazarifar, Mohsen; Amanelahi, Abbas; Ghasemizad, Alireza (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study is to examine the strategies and consequences of non-marriage among single men. Methods and Materials: The study was carried out using a qualitative approach and grounded theory methodology. The study population consisted of men whose age ranged between 33 and 45 years, considering the average age of marriage for men in the city of Kazerun in 2023 was 30.9 years. All participants were residents of Kazerun County in Fars Province. Sampling was conducted using purposive sampling based on inclusion/exclusion criteria until theoretical saturation was reached (15 participants). Data were collected through semi-structured interviews and analyzed using Strauss and Corbin’s (1998) grounded theory approach, including open, axial, and selective coding. Findings: In the open coding phase, out of 232 identified codes, 33 open codes related to strategies and 56 open codes related to consequences were extracted. These codes were categorized into different concepts during axial coding. Finally, in the selective coding phase, the main categories and related outcomes of non-marriage were identified. The most significant strategies for not pursuing marriage included improving economic conditions, enhancing mental and physical well-being, developing alternative relationships, and seeking emotional or financial bonds. On the other hand, mental and psychological consequences, objective consequences, and environmental consequences were among the major outcomes associated with prolonged singlehood in men. These included negative emotions such as depression, isolation, wasted time and energy, and economic and social problems. Conclusion: This study revealed that the decision not to marry among men is the result of a combination of psychological, social, cultural, and economic factors that influence individual choices. Based on the findings, it is recommended that social and cultural policies aimed at supporting youth and facilitating marriage are essential. Moreover, identifying and thoroughly examining cultural and social barriers to marriage could help reduce the rate of singlehood and increase the willingness to marry among young people.